Медійна війна та її вплив на суспільство: виклики для українських ЗМІ - Левицька, Анна Іванівна (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
Media warfare, sometimes known as hybrid warfare, has become a crucial component of contemporary geopolitical struggles. This form of conflict involves the use of information resources to achieve political, economic, and military objectives. Ukraine, facing Russian aggression, has emerged as a particular victim of media warfare, presenting significant challenges for Ukrainian media outlets. In this essay, we will explore how media warfare influences society and examine the tasks that Ukrainian media face in the midst of this influence.